Genetic polymorphism within HLA-A*02: significant allelic variation revealed in different populations. - Krausa, P; Brywka, M; Savage, D; Hui, K; Bunce, M; Ngai, J; Teo, D; Ong, Y; Barouch, D; Allsop, C (1995)
HLA-A2 is present at high frequency in most populations, as identified by serological and biochemical means. The value of these methods is limited by their failure to discriminate between the products of the 14 known allelic HLA-A*02 variants. The great majority of genetic polymorphism which defines the allelic variants is found in exons 2 and 3 of the A*02 genes. These exons encode the alpha-1 and alpha-2 domains of the HLA Class I molecules, and variation within the genes may influence the peptide binding specificity of the gene products of each allele. Failure to accurately assign the allelic types has implications in transplantation, in interpretation of cellular assays and in the understanding of HLA disease associations. We have developed a method for determining the 14 known alleles of HLA-A*02 by use of ARMS-PCR to determine the degree of variation of HLA-A*02 alleles in 3 different population groups. Considerable variation was found in the relative frequencies of particular A*02 alleles between Caucasian, oriental and black individuals. Our results indicate the importance of ethnic origin in terms of the expected HLA-A*02 allelic profile, and emphasize the functional significance of allele specific subtyping of HLA-A*02.